In Vitro Fertilization/Intracytoplasmic Sperm Injection with Autologous Oocytes in Healthy Women of Advanced Maternal Age: A Comparative Study Investigating Obstetric and Perinatal Outcomes Through Single Versus Double Embryo Transfer - Ellen-Elena Reinolds; Panagiotis Tsiartas; Nermin Hadziosmanovic; Kenny A. Rodriguez-Wallberg (Women's Health Reports)
Introduction: The aim of this study was to assess whether the choice between double embryo transfer (DET) and single embryo transfer (SET) in healthy women of advanced maternal age (AMA) was associated with an increased risk of adverse outcomes. Materials and Methods: Healthy women aged 39–40 years who achieved live birth after in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment between 2009 and 2020 at Karolinska University Hospital, Stockholm in Sweden, were included in this prospective, single-center cohort study. Results: A total of 310 women, who underwent IVF/ICSI treatments and achieved live births, were included in our analysis. Within this cohort, 78% of the women received SET, while 22% received DET. Nulliparity was common in both the SET (62.7%) and DET (85.3%) groups. Fresh embryo transfers were more prevalent in the DET group (91.2%) than in the SET group (31.1%). The rate of pregnancy-induced hypertension was higher in the SET group (8.3%) compared to the DET group (1.5%, p = 0.048). Furthermore, the DET group had a significantly higher rate of twin pregnancies (13.2%) compared to the SET group (0.4%). No statistically significant differences were observed in composite obstetric and perinatal complications between the SET and DET groups across all model estimates following different adjustments. Clinical Trial Registration number: ClinicalTrials.gov NTC04602962. Conclusions: While DET was more common in nulliparous women and associated with a higher rate of twin pregnancies, our analysis did not reveal significant differences in adverse outcomes between the SET and DET groups after comprehensive adjustments. Our study suggests that in the absence of co-morbidities, meticulous patient selection coupled with comprehensive maternal care can potentially mitigate potential DET-associated risks in women of AMA.